The Integration of ICT in ELT Practices: The Study on Teachers’ Perspective in New Normal Era - Maru, Mister Gidion; Pikirang, Chris Caesar; Ratu, Donal M; Tuna, Jim Ronny (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The emergence of the Covid-19 Pandemic has defined more dependence upon the involvement of ICT in EFL Class. This study investigates the integration of ICT in English teaching practices among teachers in the EFL context in a new normal setting. To achieve the aim of the study, a mixed-method approach has been applied. Thirty- two EFL teachers of junior high school who joined as members of Musyarawah Guru Mata Pelajaran (MGMP-English Teacher Regional Forum) in Bitung City, North Sulawesi, Indonesia. They have been selected as the participants for their familiarity for teaching English using the technological tools and for their teaching experience. A quantitative inquiry is carried out by distributing a questionnaire of twenty-three items adapted from two questionnaires namely those of Mailizar & Fan, and Almalki. Due to the Pandemic, the questionnaires are distributed by utilizing Google form, and then, the responses are analyzed by using SPSS tool. The qualitative data are in the forms of interview as the verification to deepen the discussion of the quantitative results. The semi-structured interview is performed and the responses are analyzed in triangulation method. The study showed that teachers’ knowledge and perception toward the integration of ICT is high. Further, this study found that despite acknowledging the importance of the enjoyment of integrating the ICT in the learning process, teachers identified the aspects of learners’ lack of technological literacy and infrastructure, and lack of motivation can be barriers for the success of the ICT integration. For such challenges, the study also revealed that teachers attempt to practice a sort of home visit and invitation learning and encouraging the making of soft skills for class activity management. These findings expectedly contribute to define the role of ICT in the current pandemic era.